The barley DIR gene family: An expanded gene family that is involved in stress responses - Luo, Ruihan; Pan, Wenqiu; Liu, Wenqiang; Tian, Yuan; Zeng, Yan; Li, Yihan; Li, Zhimin; Cui, Licao (Frontiers in Genetics, 2022)
Gene family expansion plays a central role in adaptive divergence and, ultimately, speciation is influenced by phenotypic diversity in different environments. Barley (Hordeum vulgare) is the fourth most important cereal crop in the world and is used for brewing purposes, animal feed, and human food. Systematic characterization of expanded gene families is instrumental in the research of the evolutionary history of barley and understanding of the molecular function of their gene products. A total of 31,749 conserved orthologous groups (OGs) were identified using eight genomes/subgenomes, of which 1,113 and 6,739 were rapidly expanded and contracted OGs in barley, respectively. Five expanded OGs containing 20 barley dirigent genes (HvDIRs) were identified. HvDIRs from the same OG were phylogenetically clustered with similar gene structure and domain organization. In particular, 7 and 5 HvDIRs from OG0000960 and OG0001516, respectively, contributed greatly to the expansion of the DIR-c subfamily. Tandem duplication was the driving force for the expansion of the barley DIR gene family. Nucleotide diversity and haplotype network analysis revealed that the expanded HvDIRs experienced severe bottleneck events during barley domestication, and can thus be considered as potential domestication-related candidate genes. The expression profile and co-expression network analysis revealed the critical roles of the expanded HvDIRs in various biological processes, especially in stress responses. HvDIR18, HvDIR19, and HvDIR63 could serve as excellent candidates for further functional genomics studies to improve the production of barley products. Our study revealed that the HvDIR family was significantly expanded in barley and might be involved in different developmental processes and stress responses. Thus, besides providing a framework for future functional genomics and metabolomics studies, this study also identified HvDIRs as candidates for use in improving barley crop resistance to biotic and abiotic stresses.